Measurement of the lepton charge asymmetry in inclusive W production in pp collisions at √s = 7 TeV - Chatrchyan, S. (2011)
A measurement of the lepton charge asymmetry in inclusive pp → WX production at √s = 7TeV is presented based on data recorded by the CMS detector at the LHC and corresponding to an integrated luminosity of 36 pb -1. This high precision measurement of the lepton charge asymmetry, performed in both the W → eν and W → μν channels, provides new insights into parton distribution functions. Copyright CERN.